Pulmonary MR angiography and perfusion imaging—A review of methods and applications. Issue 86 (January 2017) - Johns, Christopher S.; Swift, Andrew J.; Hughes, Paul J.C.; Ohno, Yoshiharu; Schiebler, Mark; Wild, Jim M.
Highlights: This article represents an overview of the methodology and clinical applications of pulmonary MRA and perfusion imaging. Both contrast enhanced and non-contrast enhanced metholodology for MRA and perfusion are covered. The current clinical uses and future directions of MRA and MR perfusion are discussed. Abstract: The pulmonary vasculature and its role in perfusion and gas exchange is an important consideration in many conditions of the lung and heart. Currently the mainstay of imaging of the vasculature and perfusion of the lungs lies with CT and nuclear medicine perfusion scans, both of which require ionizing radiation exposure. Improvements in MRI techniques have increased the use of MRI in pulmonary vascular imaging. Here we review MRI methods for imaging the pulmonary vasculature and pulmonary perfusion, both using contrast enhanced and non-contrast enhanced methodology. In many centres pulmonary MR angiography and dynamic contrast enhanced perfusion MRI are now well established in the routine workflow of patients particularly with pulmonary hypertension and thromboembolic disease. However, these imaging modalities offer exciting new directions for future research and clinical use in other respiratory diseases where consideration of pulmonary perfusion and gas exchange can provide insight in to pathophysiology.